2022
DOI: 10.1007/s00415-022-11226-4
|View full text |Cite
|
Sign up to set email alerts
|

Conversion from chronic to episodic migraine in patients treated with galcanezumab in real life in Italy: the 12-month observational, longitudinal, cohort multicenter GARLIT experience

Abstract: Objective To investigate in real-life the conversion from chronic migraine (CM) to episodic migraine (EM), specifically to EM with High-Frequency (HFEM: 8–14 monthly migraine days, MMDs), Medium-Frequency (MFEM, 4–7 MMDs), and Low-Frequency EM (LFEM, 0–3 MMDs), and its persistence during 1 year of treatment with galcanezumab. Methods Consecutive CM patients treated with galcanezumab completing 1 year of observation were enrolled. We collected data on MMDs, pain intensit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 36 publications
1
27
0
Order By: Relevance
“…Nonetheless, although our findings are overall in agreement with the results reported in the FRIEND study, a direct comparison cannot be done because of significant differences in the number of patients studied (67 vs. 204 in our study) and different medical histories and comorbidities. Moreover, we report similar findings to those recently published for erenumab [19][20][21] and galcanezumab [22,23] in real-world studies in both the EM and CM settings, although again methodological differences exist between studies, including the evaluation of changes in monthly migraine days (MMD) rather than MHD and the definition of the cut-off for treatment response at the level of 30% rather than 50% reduction in MHD. TA B L E 3 Changes in efficacy, disability, and quality of life outcomes at baseline (T0-trimester before initiation of therapy) and after fremanezumab treatment in patients with chronic migraine (n = 107).…”
Section: Discussionsupporting
confidence: 88%
“…Nonetheless, although our findings are overall in agreement with the results reported in the FRIEND study, a direct comparison cannot be done because of significant differences in the number of patients studied (67 vs. 204 in our study) and different medical histories and comorbidities. Moreover, we report similar findings to those recently published for erenumab [19][20][21] and galcanezumab [22,23] in real-world studies in both the EM and CM settings, although again methodological differences exist between studies, including the evaluation of changes in monthly migraine days (MMD) rather than MHD and the definition of the cut-off for treatment response at the level of 30% rather than 50% reduction in MHD. TA B L E 3 Changes in efficacy, disability, and quality of life outcomes at baseline (T0-trimester before initiation of therapy) and after fremanezumab treatment in patients with chronic migraine (n = 107).…”
Section: Discussionsupporting
confidence: 88%
“…Patients who converted from CM to EM in GARLIT achieved significantly lower MIDAS scores than those not converting to EM (50 vs 74; P = 0.005) 20 . However, even patients with no response at 3 months had clinically meaningful reductions in HIT-6 scores, pain severity, and the number of acute medications by month 6 38 . Also, in the study by Vaghi et al 24 evaluating 12 months of therapy with galcanezumab in patients with refractory CM, MIDAS scores declined from 82.8 at baseline to 27, whereas HIT-6 scores declined from 68.1 to 59.4 (both P < 0.01 vs baseline).…”
Section: Resultsmentioning
confidence: 97%
“…The GARLIT trial (a 12-month, observational, longitudinal, cohort multi-center study), which evaluated the conversion from CM to EM, revealed that 52.3% of the CM patients showed consistent conversion to EM for the entire 12 month period [ 100 ].…”
Section: Recommended Prophylactic Treatment Options In CMmentioning
confidence: 99%